KINERJA BENTONIT TERINTERKALASI HDTMA DAN KOMPOSIT BENTONIT KITOSAN SEBAGAI ADSORBEN UNTUK FENOL DAN METILEN BIRU - Yunus Fransiscus (Purifikasi, 2011)
A series of modification process to bentonite was done to obtain HDTMA intercalated bentonite and bentonite-chitosan composites. These two materials were applied as adsorbent for methylene blue and phenol removal. Suspension of 1% HDTMA-Cl surfactant and bentonite was made from bentonite/water ratio of 20g/100mL, with pH adjustment, warming, precipitation, and washing processes. About 5 g of bentonite was mixed with 1% v/v acetic acid and deacetilated chitosan. After being stirred within 12 hours, the solution was washed, filtered, and dried. Phenol and methylene blue adsorbates were prepared as stock solution. The required concentrations were prepared by diluting the mother liquors with aquadest. The experiment was conducted in batch system using OMNIFIT adsorption column. The solution was recirculated from the adsorption column to the reservoir tank. The feeding flow rate and the amount of adsorbent were set constant at a flow rate of 1 mL/min. Initial concentrations of phenol and methylene blue were varied from 10 to 250 mg/L. Sampling was done every 5 minutes in the first 30 minutes, and continued every 15 minutes, until the system reached equilibrium state. Sample analyses were carried out by using UV-spectrophotometer. The results showed that the bentonite-chitosan composite had higher phenol and methylene blue adsorption capacity than that of the HDTMA intercalated bentonite. The adsorption capacities of bentonite-chitosan composites were 65 mg/g and 95 mg/g for phenol and methylene blue respectively. Whereas, HDTMA intercalated bentonite showed adsorption capacities of 35 mg/g for phenol and 38 mg/g for methylene blue. Freundlich model was most appropriate with the obtained data. This model explained that interaction between adsorbent and adsorbate were mainly influenced by physical reaction.